2001
DOI: 10.1002/app.1706
|View full text |Cite
|
Sign up to set email alerts
|

Study of the thermal properties and relaxation transitions in tetrafluoroethene‐ethene copolymers

Abstract: Copolymerization of tetrafluoroethene (TFE) with ethene (E) in wateralcohol medium initiated by 2,2Ј-azo-bis-izobutyronitrile (AIBN) at 338 K and 4.2 MPa was conducted in an autoclave by employing a semiflow procedure to feed the comonomers. The thermal properties of the copolymers under both the static and dynamic conditions of thermal treatment in air (ageing) were studied. The most pronounced changes in the initial temperature of destruction were observed for the compositions containing more than 42 mol % T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…However, such a peak does not appear in the spectrum for pristine ETFE (Fig. 1b) [15], thus verifying that thermal oxidation has occurred. Such thermal destruction behavior could originate from end groups, chain Fig.…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…However, such a peak does not appear in the spectrum for pristine ETFE (Fig. 1b) [15], thus verifying that thermal oxidation has occurred. Such thermal destruction behavior could originate from end groups, chain Fig.…”
Section: Resultsmentioning
confidence: 70%
“…Kostov and coauthors revealed similar results, but obtained a reaction order and E d value of 1.04 and 174 kJ/ mol, respectively. Meanwhile, they also found that ETFEs undergo low-level thermal oxidation (a mass loss of >0.5% was detected below 548±5 K, after thermal oxidation in air for 5 h), whereas IR spectra did not support any significant changes in the functional groups of ETFEs after thermal aging [15]. Loginova and coworkers investigated the thermal decomposition behavior of ETFE [32].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Consequently, ETFEs are intensively explored on the molecular parameters and microstructures [3][4][5][6][7][8][9], thermal and crystallization behaviors [10][11][12][13], and steady-state viscous properties [14][15][16]. However, its capillary flow and high-shear rheological behaviors are scarcely reported, despite their fundamental and technical importance.…”
Section: Introductionmentioning
confidence: 99%